Predictors of mortality among individuals with advanced HIV disease in a contemporary Brazilian cohort - Nicole Reis; Omar Sued; Tarsila Vieceli; Diego R. Falci; Larissa R. Silva; Pedro M. Fonseca; Renata B. A. Soares; Cassia S. M. Godoy; Marineide G. Melo; Nayla A. Hatem; Ana C. G. Castelo; Freddy Perez; et al. (Revista Panamericana de Salud Pública)
Objective. To identify clinical characteristics and risk factors associated with mortality, with a focus on opportunistic infections (OIs), in patients with advanced HIV in Brazil. Methods. A prospective cohort study was conducted in five Brazilian tertiary hospitals, including 419 adults with advanced HIV. Baseline demographic and clinical data were collected during hospital admission, and participants were screened for tuberculosis, cryptococcosis, and histoplasmosis using rapid diagnostic tests. Participants were followed for 90 days to assess mortality, with causes of death classified using the Coding of Death in HIV (CoDe) protocol. Statistical analysis identified the variables associated with mortality. Results. The median CD4 count was 66 cells/mm³, and the median HIV viral load was 104 887 copies/mL. After 90 days, 18.1% of participants had died. ART-naive status, mental confusion, anemia, and elevated creatinine levels were strongly associated with mortality. OIs were diagnosed in 45.6% of participants, with severe histoplasmosis and cryptococcal meningitis significantly increasing the risk of mortality. Social determinants, such as sex, race, gender, and education level, did not have a significant impact on mortality, but socio-economic factors influenced health care access. Conclusion. Early HIV diagnosis and continuous ART are essential to reduce mortality. Public health strategies should prioritize improving HIV testing, treatment adherence, and addressing social disparities to mitigate health care inequalities.